LEGAL BASIS FOR THE REGULATION OF LAND RELATIONS IN THE UKRAINIAN COSSACK STATE (SECOND HALF OF THE XVII – XVIII CENTURY) (Law and Safety, 2018)
The uniqueness of the Cossack land use system was emphasized, which was based on customary law and differed significantly from both Western European models and Russian “communal” land use. The Cossacks hardly opposed any attempts by the prosperous class to occupy the dominant position in the political system due to large land ownership, which was contrary to the traditions of Ukrainian landownership and democracy.The idea of legal equality within land relations was initially cultivated in Zaporozhie. The institution of a sole proprietor of the land plot with a hereditary scheme of transferring ownership rights to it was contrary to the legal culture of the Cossacks. However, starting from the middle of the XVII century there was a tendency for a transition from small-proprietary landed estates to medium and large landownership of a relatively small part of the prosperous class of Cossacks. In this regard, the colonels and representatives of the Hetman dynasties emphasized the expansion of the rights of large landowners and the narrowing the rights and freedoms of small landowners.The author has focused attention on the fact that the subjects of medium and large landed property, i.e., the prosperous class of Cossacks and the registered Cossacks were, at that historical stage, the carriers of the advanced legal thought of European civilization with the emerging commodity capitalist production, while small landownership was oriented towards self-sufficiency of households.Left-bank Ukraine, due to a balanced system of land relations, achieved a high level of well-being, even by European standards, by the beginning of the XVIII century. But the invasion of Russian legislation into Ukrainian legal area, the presence of the governor and “military people” led to the complete subordination of the Ukrainian lands to the tsarist autocracy and the scrapping of the unique state and legal system of the Hetman era.
Keywords: Hetman era; land relations; prosperous class of Cossacks; nobility; Russian empire; Rights, according to which Little Russian people are at law.